Melatonin protects against ionizing radiation-induced oxidative damage in corpus cavernosum and urinary bladder in rats - (:unkn) unknown (WILEY, 2004)
The objective of this study was to examine the potential radioprotective properties of pharmacological doses of melatonin on corpus cavernosum and bladder tissues of whole-body irradiated (IR) rats. A total of 32 male Sprague-Dawley rats were exposed to irradiation performed with a LINAC which produced 6 MV photons at a focus 100 cm distant from the skin. Under ketamine anesthesia, each rat received a single whole-body dose of 800 cGy. Immediately before and after IR, rats were treated with either saline or melatonin (20 and 10 mg/kg, i.p.) and decapitated at 12 hr after exposure to irradiation. Another group of rats was followed for 72 hr after IR, where melatonin injections were repeated once daily. Tissue levels of malondialdehyde (MDA), an index of lipid peroxidation, and glutathione (GSH), a key antioxidant, were estimated in corpus cavernosum and urinary bladder. Tissues were also examined microscopically. The results demonstrate that both 12 and 72 hr following IR, tissue levels of MDA were elevated (P < 0.001), while GSH levels were reduced (P < 0.01) in both tissues. On the other hand, melatonin reversed these changes significantly (P < 0.05-0.01), concomitant with the improvement in histological appearances. Our results show that whole-body irradiation causes oxidative damage in the tissues of the genitourinary system. As melatonin administration reversed oxidative organ injury, as assessed by biochemical and histopathological findings, it is suggested that supplementing cancer patients with adjuvant therapy of melatonin may have some benefit for successful radiotherapy.
Keywords: bladder; corpus cavernosum; glutathione; irradiation; lipid peroxidation; LIPID-PEROXIDATION; REPERFUSION; ISCHEMIA; STRESS; INJURY; OXYGEN; ORGAN; DNA